AudaCITY: A Capacity-Building Research Method for Urban Sustainability Transformation - Keeler, Lauren Withycombe; Bernstein, Michael J.; Nelson, John P.; Kay, Braden R. (Frontiers in Sustainable Cities, 2022)
The scale and urgency of sustainability problems the world over has led to calls for sustainability transformations in cities, regions, and countries. Such calls for transformation are underlain by a persistent knowledge-to-action gap between scientific knowledge production, policy, and practice. To rise to the challenges of sustainability and resilience, municipal administrators need to set evidence-based and ambitious sustainability targets and develop strategies to achieve them. Simultaneously, transdisciplinary sustainability science researchers need to generate scientific knowledge to further enable cities along pathways of transformation. This paper details a collaborative backcasting game, AudaCITY, developed to build transformative capacity in city administrations while also generating deep contextual knowledge to inform a transformative sustainability science research agenda. We present AudaCITY’s key features, potential applications and adaptations, and exemplary outputs and outcomes for cities and researchers. We conclude with recommendations for adopting and adapting AudaCITY for use in action-oriented and transformational sustainability science and capacity building.